2020
DOI: 10.3390/sym12050862
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Task Assignment Problem with Maximum Benefits in Volunteer Computing Platforms

Abstract: As a type of distributed computing, volunteer computing (VC) has provided unlimited computing capacity at a low cost in recent decades. The architecture of most volunteer computing platforms (VCPs) is a master–worker model, which defines a master–slave relationship. Therefore, VCPs can be considered asymmetric multiprocessing systems (AMSs). As AMSs, VCPs are very promising for providing computing services for users. Users can submit tasks with deadline constraints to the VCPs. If the tasks are completed withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Xu et al 37 proposed a VC‐based task scheduling to maximize volunteers' benefits. Initially, all the tasks are scheduled in the list based on their priority and deadline using the maximum benefit scheduling algorithm which provides more benefits to volunteer devices as only allowable tasks are completed while the others are pruned out.…”
Section: Literature Surveymentioning
confidence: 99%
“…Xu et al 37 proposed a VC‐based task scheduling to maximize volunteers' benefits. Initially, all the tasks are scheduled in the list based on their priority and deadline using the maximum benefit scheduling algorithm which provides more benefits to volunteer devices as only allowable tasks are completed while the others are pruned out.…”
Section: Literature Surveymentioning
confidence: 99%
“…The authors of [23] suggested research on the maximum gains for volunteer computing platforms (VCPs). VCPs can be considered asymmetric multiprocessing systems (AMSs).…”
Section: Related Workmentioning
confidence: 99%
“…Then, the algorithm arranges tasks in non-increasing order based on their cost function V, grouped by shared resources (lines [23][24][25][26][27][28][29][30][31][32]. The output of BABP is the task set where the tasks are sorted depending on their cost function.…”
Section: Blocking-aware-based Partitioning (Babp) Algorithmmentioning
confidence: 99%
“…Main aim of JSP is to minimize the makespan [10]. In multi-objective optimization, two or more conflicting objectives are optimized with a given set of constraints simultaneously.…”
Section: A Related Workmentioning
confidence: 99%